Public Sociology As Educational Practice : Challenges, Dialogues and Counter-Publics - Scabdrett, Euring (Book collections on Project MUSE., 2020)
Leading academics reflect on concepts and aspects of public sociology education in this perceptive collection of case studies, linked by critical dialogue between contributors. They consider publics, practices and special knowledges in the field, and go beyond academia's boundaries to explore the purposes and targets of sociological knowledge.